﻿Combination of selected Thai traditional pain relief medicinal plants with anti-inflammatory abilities in a protein denaturation assay - Orawan Theanphong; Pathom Somwong (Pensoft Publishers, 2022)
Crateva adansonii DC, Maerua siamensis (Kurz) Pax, and Mallotus repandus (Willd.) Müll. Arg. have long been used as ingredients in compound herbal medicines to relieve pain in Thailand. In this study, an albumin denaturation inhibition experiment was used to assess the anti-inflammatory properties of the ethanolic extracts of these plants and their mixture. Lupeol, the active molecule responsible for the anti-inflammatory activity, was chosen as a chemical marker for the extracts. All plant extracts demonstrated anti-inflammatory potential. Their IC50 values ranged from 1.19 to 7.31 mg/mL. This blend showed the strongest anti-inflammatory effect, with a 0.5-fold increase in activity when compared to diclofenac. Lupeol, an anti-inflammatory agent, is one of the chemical constituents of the selected medicinal plants. Its content ranged from 0.04 to 8.60% w/w, as determined by HPLC in this study. It means that the plants, alone and in combination, are a good source of herbs for further pharmacological study and product development.